Nexus between Foreign Capital Inflows and Human Capital Development in Nigeria - Oloke, Emmanuel; Olabisi, Faseesin; Johnson, Adebayo Akanbi; Awofala, Hassan Taiwo; Aderemi, Timothy Ayomitunde (EuroEconomica, 2022)
This aim of study is on the nexus between foreign capital inflows and human capital development in Nigeria spanning from 1990 to 2020. This study relied on secondary data which was sourced from the World Development Indicators. Consequently, the FMOLS method was utilized to analyze the data. Based on the findings erupted from this study, trade openness has a negative and significant relationship with human capital development. In the same vein, FDI and portfolio investment have a significant inverse relationship with human capital development in Nigeria. However, official development assistance has a direct relationship with human capital development, the relationship is significant at 10 percent level of significance. And exchange rate has a positive and significant relationship with human capital development. Both external debt and remittances have insignificant positive relationship with human capital development in Nigeria. In a nutshell, the majority of the inflows of foreign capital in Nigeria have a significant and negative relationship with human capital development in this study. Steaming from the above findings, this study recommends that the policymakers in Nigeria should deploy the inflows of foreign capital in the direction of the human development oriented programmes in the country.